Analysis of The Role of Store Atmosphere in Influencing Consumer Purchasing Decisions at XYZ Cooperative - Fahreza, Mohammad; Rahayu, Agus; Hendrayati, Heny (International Journal of Business, Economics, and Social Development, 2024)
A cooperative is a business entity consisting of individuals and legal entities that is based on the principles of kinship and economic democracy and is a means of increasing economic progress for cooperative members and the community. This research aims to determine the influence of Store Atmosphere on consumer purchasing decisions at the XYZ Bandung Cooperative. Several members explained that the reason for reducing purchases of goods at the XYZ Cooperative was because they felt that some goods were not given enough attention, such as whether the goods on display were still suitable for consumption or not, communication of information either through social media or information boards was still not working well, the prices of goods were not high. expensive and less affordable for members and other consumers to buy. The research method used was quantitative, the sampling technique used probability sampling and a sample of 43 domestic and foreign tourist respondents was obtained. The analytical tool used was simple regression analysis and the hypothesis used a significance test using the SPSS analysis tool. The results of this research explain that the Store Atmosphere has a positive and significant influence on purchasing decisions at the XYZ cooperative and several dimensions of the Store Atmosphere such as the exterior, store layout and interior appearance have a positive and significant influence on purchasing decisions at the XYZ cooperative. There needs to be more attention from the management of the XYZ cooperative in paying attention to the shop atmosphere so that consumers, especially members, can increase their purchasing decisions at the XYZ Cooperative.